Graphene: Temporospatial Control of Graphene Wettability (Adv. Mater. 4/2016). Issue 4 (21st January 2016) - Vijayarangamuthu, Kalimuthu; Ahn, Seungbae; Seo, Hyungtak; Yoon, Sang‐Hee; Park, Cheol‐Min; Jeon, Ki‐Joon
Abstract : The reversible migration of adatoms along a basal plane of graphene under electrical bias is demonstrated experimentally by K.‐J. Jeon and co‐workers, as described on page 661, using the intensity ratio of the G and G' Raman modes to determine the migration of oxygen adatoms. The inside cover demonstrates the electromigration of the oxygen adatoms (red balls) on the basal plane of the graphene under electrical bias. The oxygen adatoms migrate in the direction of electron flow as indicated by the tails on the red balls.